Shared principles of islamic-catholic dialogue: a comparative thematic analysis of theological documents - Konstantinus Bahang; David Dapi (Lentera Negeri, 2026)
This study analyzes shared principles of interreligious dialogue in Islam and Catholicism using an interpretive qualitative design that combines library research, document study, qualitative content analysis, thematic analysis, and comparative interpretation. The corpus comprised five primary documents—the Qur'an, Nostra Aetate, Dialogue and Proclamation, A Common Word Between Us and You, and the Document on Human Fraternity for World Peace and Living Together—and 38 secondary scholarly sources. Secondary literature was identified through Scopus with Sider Scholar support using keywords on Islam–Catholic dialogue, Muslim–Christian dialogue, interreligious dialogue, Nostra Aetate, A Common Word, human fraternity, and dialogue of life. Peer-reviewed publications from 2007–2026 were prioritized, while older foundational sources were retained when directly relevant. Units of meaning were coded deductively across theological foundation, human dignity, religious freedom, openness, identity honesty, rejection of violence, cooperation, justice, and peace, and inductively for emerging themes. Coding was conducted by one researcher; reliability was supported through repeated coding, an audit trail, source triangulation, and comparison of data, interpretation, and conclusions. Three findings emerged: both traditions connect faith with human dignity and peace; authentic dialogue requires freedom, equality, listening, and honest identity without mixing doctrines; and dialogue must extend into social cooperation, education, humanitarian service, advocacy, conflict resolution, and digital literacy. The shared ground is therefore ethical-relational rather than complete theological equivalence.